Cyber-physical flexible wing for aeroelastic investigations of stall and classical flutter. (November 2016) - Fagley, Casey; Seidel, Jürgen; McLaughlin, Thomas
Abstract: The fluid–structure interactions of a finite aspect ratio, cantilevered, flexible wing were investigated using a cyber-physical system to virtually augment the torsional dynamics of the wing. Cyber-physical systems (CPS), which have recently been pursued by a small number of research groups, have proven to be a very useful mechanism to interrogate the fluid–structure interaction parameter space. The premise of a CPS is to use dynamic feedback control to make a system behave according to desired equations of motion. Systems are composed of embedded hardware and software coupled with real-time computing to give the user the flexibility to quickly explore a range of structural parameters. With the advancement of modern control theory, robotics and embedded systems, CPSs integrate both simulation and physical properties into a smart structure which can be used to push the boundaries of research investigations. The CPS in this work allows for the investigation of dynamic aeroelastic instabilities of a three-dimensional, flexible, rectangular planform wing. Two dynamic instability regimes are observed: first, stall flutter, in which the torsional or pitch mode is excited through the dynamic stall process, and second, coupled (or classical) flutter, in which the pitch mode couples with the bending mode. By varying the torsional stiffness and therefore the frequency of torsional versus bending oscillations of the wing, both of these regimes can be attained at the same aerodynamic conditions using the CPS.